Enhanced morphological transformation of human lung epithelial cells by continuous exposure to cellulose nanocrystals. (July 2020) - Kisin, E.R.; Yanamala, N.; Rodin, D.; Menas, A.; Farcas, M.; Russo, M.; Guppi, S.; Khaliullin, T.O.; Iavicoli, I.; Harper, M.; Star, A.; Kagan, V.E.; et al.
Abstract: Cellulose nanocrystals (CNC), also known as nanowhiskers, have recently gained much attention due to their biodegradable nature, advantageous chemical and mechanical properties, economic value and renewability thus making them attractive for a wide range of applications. However, before these materials can be considered for potential uses, investigation of their toxicity is prudent. Although CNC exposures are associated with pulmonary inflammation and damage as well as oxidative stress responses and genotoxicity in vivo, studies evaluating cell transformation or tumorigenic potential of CNC's were not previously conducted. In this study, we aimed to assess the neoplastic-like transformation potential of two forms of CNC derived from wood (powder and gel) in human pulmonary epithelial cells (BEAS-2B) in comparison to fibrous tremolite (TF), known to induce lung cancer. Short-term exposure to CNC or TF induced intracellular ROS increase and DNA damage while long-term exposure resulted in neoplastic-like transformation demonstrated by increased cell proliferation, anchorage-independent growth, migration and invasion. The increased proliferative responses were also in-agreement with observed levels of pro-inflammatory cytokines. Based on the hierarchical clustering analysis (HCA) of the inflammatory cytokine responses, CNC powder was segregated from the control and CNC-gel samples. This suggests that CNC may have the ability to influence neoplastic-like transformation events in pulmonary epithelial cells and that such effects are dependent on the type/form of CNC. Further studies focusing on determining and understanding molecular mechanisms underlying potential CNC cell transformation events and their likelihood to induce tumorigenic effects in vivo are highly warranted. Highlights: CNC may have the ability to influence neoplastic-like transformation events. Proliferative responses are in agreement with levels of inflammatory cytokines. Exposure to CNC gel or powder leads to distinct alterations in cellular responses. Distinctive differences in response were found after exposure to TF compare to CNC.